IMPACT OF ROAD CONFLICTS ON DRIVER PERFORMANCE AT TWILIGHT: Array - Prasolenko, O. (Municipal economy of cities (Technical science), 2019)
Most of the road accidents (road traffic accidents) in the world are due to driver's fault. The reason is usually the driver's wrong actions in difficult road conditions, dangerous road traffic situations that depend on many factors driving the situation. Particularly necessary to indicate an accident in the dark and in the conditions of evening twilight in the autumn-winter period. In these conditions, driving requires the driver to concentrate attention, the ability to maintain speed within his own functional comfort, and make prompt decisions about changing the trajectory and speed according to the road conditions. About 90 percent of the drivers receives visual information. In the dark time of day, the illumination of the road is of great importance to the sight. In order for the eyes to recognize the object, a certain level of illumination is required. Subjects can be recognized by a silhouette - when the brightness of an object is lower than the brightness surrounding its background, or when the brightness interferes more with the surrounding background. The greatest difficulties for the driver occur when sharp changes in the illumination of the road, when moving in low light conditions. The rapid change in the levels of illumination causes irritation of the retina of the eye, and temporary glare occurs. The glare time varies widely and can take from a few seconds to a few minutes. Changing the lighting also affects the reaction time of the driver. Untimely or inaccurate reactions often lead to road accidents. The driver can not always see the trajectory of other cars or see the suddenly emerging pedestrian on the roadway. The reaction time in this case may vary from 0.4 to 2.5 s wide, depending on the professional experience and the individual psycho-physiological characteristics of the driver. The paper presents an approach to determining the impact of conflict situations on city streets on driver performance in the dark at the time of the day. The laws of changing the illumination in the evening conditions and the parameters of interaction of drivers in the dark time of day are investigated. The approach for determination of parameters of interaction of the driver with the road environment on the basis of the method of conflict situations is proposed. The indexes of change of the functional state of the driver and the energy cost when entering into various conflict situations on city streets are established at the dark time of day in the evening twilight.